Assessing public awareness on the roles of tribunal of home buyers claims (TTPR) / Nadzirah Ishak - Ishak, Nadzirah (Faculty of Architecture, Planning and Surveying, 2013)
Tribunal for Homebuyers Claim plays an important role for the homebuyers. Nowadays, many buildings such as house lack in many perspective such as quality. The low quality of the building will contribute to the damages and defects on the building. There are many factors that will contribute to this problem. The factors may caused by the natural factors such as dampness, whether condition and fungus. Any other factors may caused by the low quality of materials and also poor workmanship. Without the good evidence, the homebuyers cannot make an accuse to any other party. The Tribunal for Homebuyers Claim exists to act as the court to determine the homebuyer’s claim in easy, fast and cheap way. The Tribunal also gives a change to homebuyers to stand for their right. The objective of this study is to identify the awareness of Tribunal for Homebuyers Claim among the public. The respondents are staff workers of UiTM Shah Alam that will conclude the construction, education and management fields. These three fields will be focused on the three place which are: Hotel Shah Alam (INTEKMA Resort), Public Works Facilities Management and Language Centre. Finally, the researcher found that the awareness of public about the Tribunal for Home Buyers Claim is very low level. The awareness of public still low and need to be improve with many implementation of approach to this matter.